Analysis of predictors of success in the MRCP (UK) PACES examination in candidates attending a revision course - Bessant, R (BMJ Group, 2006)
OBJECTIVE: To determine factors that predict success of candidates taking a revision course in preparation for the MRCP (UK) PACES (practical assessment of clinical examination skills) examination. DESIGN: A questionnaire survey of candidates attending a PACES revision course. Results were correlated with subsequent pass lists published by the Colleges of Physicians SETTING AND SUBJECTS: Candidates attending courses in June and October 2002. In total, 523 candidates completed questionnaires, evenly balanced between UK and overseas graduates. RESULTS: Of 483 candidates who took the examination immediately after the course, 219 (45.3%) passed. UK graduates were more likely to pass (67.0%) than overseas graduates (26.2%) (p = 0.003, odds ratio 5.72). For UK graduates, pass rates were higher for white candidates (73%) than for ethnic minorities (56%) (p = 0.012, OR 2.15) and for those who passed at the first attempt in the MRCP (UK) part 2 written paper (p = 0.003, OR 2.90). For overseas graduates, those who had been qualified for less than eight years were more likely to pass (p = 0.001, OR 2.78). More overseas (45.7%) than UK (30.8%) graduates were confident that they would pass, but confidence did not predict success. CONCLUSION: Among candidates taking a revision course, UK graduates are more likely to pass the PACES examination than non‐UK graduates. Ethnic minority UK graduates seem to have a significantly poorer success rate, although this requires confirmation in an independent sample. If confirmed, these differences merit further investigation to assess whether they reflect genuine differences in ability.